Lichens of the Terra Nova bay area, Northern Victoria Land - Castello, Miris (EUT Edizioni Università di Trieste, 2003)
57 lichen species are reported from the Terra Nova Bay area (Northern Victoria Land, continental Antarctica), on the basis of collections from the Italian Antarctic Expeditions 1987-1996. 51 of them were identified to species level. A key for their identification is provided. Morpho-anatomical descriptions and nomenclatural, taxonomic and phytogeographical remarks are given for each taxon. Blastenia viridans Js. Murray is reduced to synonymy with Caloplaca athallina Darb.